Study on Plastic Waste for Replacement of Coarse Aggregate With Soft and Hard Plastic in Concrete - Sharma, Bhanu; Tiwari, Richa; Maurya, Lalit; Chitranash, Shubham; Kumar, Mukesh; Sharma, Anuj Kumar (AMC Indian Journal of Civil Engineering, 2020)
There is an enormous issue of plastic in environment. Disposal of waste plastic from households has become a big problem for agencies in cities. Plastic waste management can be an international problem as plastic is a non-perishable substance. Plastic waste includes single use plastic such as plastic bottles, single use straw, food containers, and alternative plastic materials. Plastic cannot be burnt by burning, as a result it causes major pollution and releases harmful gases like dioxide, dioxins ,furans, and metals. These emissions cause metabolic process issues. Dumping huge amount of plastic onto land reduces the fertility of soil and causes soil pollution. Plastic waste primarily consists of Low Density Polyethylene (LDPE). Plastic waste is placed within the ash can and plastic bear evacuation blocksitor the area units are burnt on the margin, which produces pollution. Industrial waste from polypropene (PP) and polythene terephthalate (PET) were studied at various replacements in the vicinity of the standard aggregates of concrete. Polypropene is a powerful, rigid, and crystalline thermoplastic which is known as exhausting plastic. Polythene terephthalate is a soft ,flexible plastic that is usually used for plastic bottles. In our analysis, the only aim is to study the suitability of plastic as a replacement of coarse mixture in concrete with soft and exhausting plastic each, and to get the replacement with maximum compressive strength in concrete. Suitable mixtures were used for the preparations of the concrete.